Testing the existence and direction of "spill-over" of mussel recruits beyond the boundaries of marine protected areas - Ludford, Adam (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2011)
Landscape ecology helps in predicting the influence of habitat fragmentation on populations. Marine protected areas (MPAs) are expected to create areas of good quality patches and so improve connectivity among shores. MPAs are believed not only to protect adult populations, but also to enhance recruitment both within MPAs and on surrounding exploited shores, therefore improving their ability to recover from overexploitation. As such, MPAs are a preferred management tool for the conservation of natural populations. Although MPAs have been demonstrated to enhance adult abundances, little work has been done on their ability to provide so called "spill-over" of recruits nor has the generality of the influence of MPAs been investigated in a single region with multiple control sites. The Transkei region, on the east coast of South Africa, and the intertidal mussel, Perna perna, offer an ideal system to test the generality of the influence of MPAs on surrounding shores, due to the presence of multiple MPAs and exploited control sites. Patterns of adult abundance were surveyed at four MPAs and two comparably sized exploited control sites. Adult abundances were, in general, found to be higher within MPAs than at exploited control sites, with adult abundances decreasing towards the edge of MPAs and decreasing even more on the outside shores. To simplify the sorting procedure for samples of mussel recruits, a new method using fractionated elutriation was devised and tested. This new method was found to be more accurate, although not statistically significant but also substantially more time consuming. The increase in accuracy although not statistically significant could be biologically significant, especially when looking at low numbers. This new method could, therefore, be very useful especially when [...] is low. Recruitment was estimated over three months during the main reproductive season at two of the MPAs and at appropriate control sites. I predicted that recruitment patterns would mirror the patterns found in adult abundances and that there would be directionality in patterns of recruitment, with northern sites having greater recruitment due to the direction of near-shore ocean currents. Contrary to this, there were no correlations between adult abundance and recruitment for any of the months or sites, with no clear spatial pattern of recruitment in any of the three months. There was, however, a slight trend of greater recruitment at northern sites. To explain the lack of consistency in recruitment and adult abundances, wind data were used to examine the near-shore surface currents in this area, with theoretical surface currents showing similar patterns to those observed for recruitment. From a landscape perspective, the good patches created by MPAs supply recruits to the surrounding matrix but the low quality of habitat in the matrix prevents rehabilitation. The quality of the matrix must therefore be first improved by reseeding these shores. These results emphasise that while MPAs may function in protecting adult abundances, their influence on supplying recruits and hence recovery of near-by exploited shores may be overestimated. This lack of influence on near-by exploited shores highlights the need for reseeding of shores in conjunction with suitable management plans.
Keywords: Marine parks and reserves -- South Africa -- Transkei; Marine resources conservation -- South Africa -- Transkei; Mussels -- Ecology -- South Africa -- Transkei; Mexilhao mussel -- Reproduction -- South Africa -- Transkei; Mexilhao mussel -- Behavior -- South Africa -- Transkei